Correction to: A head-to-head comparison of [68Ga]Ga-DOTATATE and [68Ga]Ga-FAPI PET/CT in patients with nasopharyngeal carcinoma: a single-center, prospective study. - Zheng, Jieling; Wang, Guochang; Ru, Qian; Yang, Yun; Su, Li; Lv, Wenlong; Ke, Chunlin; Wang, Peirong; Liu, Xiaohui; Zhang, Li; Liu, Feng; Miao, Weibing (European Journal of Nuclear Medicine & Molecular Imaging, 2024)
This document is a correction notice for an article titled "A head-to-head comparison of [68Ga]Ga-DOTATATE and [68Ga]Ga-FAPI PET/CT in patients with nasopharyngeal carcinoma: a single-center, prospective study." The correction acknowledges that the name of Dr. Feng Liu was not included as a co-corresponding author in the original article. Additionally, the original version of Figure 4 in the article was incorrect, and the correct version is provided in the correction notice. The publisher, Springer Nature, maintains a neutral stance on jurisdictional claims and institutional affiliations.